Wandering soul : the Dybbuk's creator, S. An-Sky - Safran, Gabriella, 1967- (Belknap Press of Harvard University Press, 2010)
In The Dybbuk, the mystical play at the center of modern Yiddish and Hebrew theater, the hero experiments with Kabbalah, dies, then rises from the dead to possess the woman he loves. The play's author was just as restless and rebellious. Shloyme-Zanvl Rappoport, known by his pen name, S. An-sky, was a Russian and Yiddish journalist, a revolutionary propagandist, and a pioneering ethnographer who lived with Russian miners and Hasidic Jews. Wandering Soul is the first biography of An-sky. Using all his writing in Russian and Yiddish, his drafts, and his revealing letters, Gabriella Safran explores his life, his work, and through him the rich world of the Russian Jews.